2019
DOI: 10.1186/s12870-019-2169-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression among three sex types reveals a MALE STERILITY 1 (CpMS1) for sex differentiation in papaya

Abstract: BackgroundCarica papaya is a trioecious plant species with a genetic sex-determination system defined by sex chromosomes. Under unfavorable environmental conditions male and hermaphrodite exhibit sex-reversal. Previous genomic research revealed few candidate genes for sex differentiation in this species. Nevertheless, more analysis is still needed to identify the mechanism responsible for sex flower organ development in papaya.ResultsThe aim of this study was to identify differentially expressed genes among ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 93 publications
0
8
0
2
Order By: Relevance
“…Although transcriptome analyses focusing on the sexual differentiation of papaya have revealed several genes related to the biosynthesis of plant hormones and ABA, ROS, and auxin signaling pathways, most of the DAPs observed between the sexes in the present study were involved in carbohydrate metabolism, phenylpropanoid biosynthesis, and sporopollenin biosynthesis 13 , 32 , 33 . Furthermore, the genes encoding these proteins were all mapped to autosomal chromosomes or the autosomal region of chromosome 1.…”
Section: Discussionmentioning
confidence: 55%
“…Although transcriptome analyses focusing on the sexual differentiation of papaya have revealed several genes related to the biosynthesis of plant hormones and ABA, ROS, and auxin signaling pathways, most of the DAPs observed between the sexes in the present study were involved in carbohydrate metabolism, phenylpropanoid biosynthesis, and sporopollenin biosynthesis 13 , 32 , 33 . Furthermore, the genes encoding these proteins were all mapped to autosomal chromosomes or the autosomal region of chromosome 1.…”
Section: Discussionmentioning
confidence: 55%
“…ASE analysis has several advantages over differential gene expression (DGE) analysis. The latter has been widely used to identify genes differentially expressed between different tissues of the same genotype, between the same tissues of different genotypes, or the same tissue across time courses (Klumb et al ., 2020; Nishitani et al ., 2020; Wang et al ., 2020; Zerpa‐Catanho et al ., 2019). However, DGE does not address allele specificity.…”
Section: Discussionmentioning
confidence: 99%
“…LRR-RLKs act upon the substrates which control floral organ abscission ( Cho et al, 2008 ), and some of them were found to be involved in the floral growth and development of S. japonicus ( Li J. et al, 2019 ). In Carica papaya , two LRR-RLK genes were upregulated in its female buds and may be involved in that plant’s sex differentiation ( Zerpa-Catanho et al, 2019 ). The C2H2 TFs have been previously documented to play important roles in various processes during plant development, including sex determination.…”
Section: Discussionmentioning
confidence: 99%